Sound propagation throughout the orchestra. Measurement, simulation, and modelling - Porcinai, Emanuele; Weinzierl, Stefan (Applied acoustics, 2025)
One of the main challenges in predicting the room acoustic conditions on a stage is taking into account the presence of the ensemble and its effect on sound propagation. In a scenario where diffraction effects are dominant and the shape and arrangement of obstacles are not only highly complex but also time-varying, geometric acoustic methods do not yet provide sufficient accuracy for calculating room acoustic parameters or for auralisation. To address this limitation, anechoic measurements from a group of seated subjects were combined with Boundary Element Method simulations at lower frequencies to obtain broadband insertion loss values for a total of 104 paths within a typical orchestra setup. These transfer functions have been converted into a Diffraction-Induced Attenuation by Seated Persons FIR Database, which includes linear phase approximations of the direct sound as well as floor reflections, and reproduces the attenuation that occurs between players in an orchestra. Based on these filters, a parametric model was developed to predict insertion loss within different groups of seated people. This can be used in geometric acoustic simulations and auralisations to account for insertion loss within different groups of seated people, as they occur in many acoustically relevant everyday situations. •Comprehensive database of insertion loss measurements and simulations between orchestra players under anechoic conditions.•New parametric model predicts insertion loss within seated groups, aiding auralisation for stage acoustics research.•Study accounts for the significant effects of musicians' movements on sound propagation, allowing for realistic auralisation.